PSYCHOLOGICAL WELL-BEING OF FAMILIES WITH A CHILD WITH INTELLECTUAL DISABILITIES - P. A. Kislyakov; E. A. Shmeleva (Russian State Vocational Pedagogical University, 2017)
Introduction. The culture of parents, family constellation and the atmosphere in the family, including psychological well-being of all its members have a great impact on forming of the identity of a child. The study of psychological well-being of parents with children with intellectual disabilities, allows us to select the most important areas of work with the family, effectively distribute the efforts of experts to meet the communication, medical, educational and other needs of families.The aim of this research is to analyze the state of psychological well-being of parents of the special boarding school children as a factor of their socialization.Methods. A standardized scale of subjective wellbeing (authors Perrudet-Badoux, Mendelssohn and Chiche, adapted by V. M. Sokolova) is used to determine the components of the psychological well-being of parents of mentally deficient children. The technique «A scale of subjective well-being» in author's adaptation is applied to determination of the level of psychological well-being of school students.Results. 58 parents from 53 families and 60 children of early teenage age (12-13 years) having the diagnosis of F70 (minor mental retardation) or F71 (moderate mental retardation) participated in the research; it shows that the comprehensive social and psychological support of a family aimed at providing psychological well-being of parents (their legal representatives) in the conditions of correctional boarding school becomes a factor of positive socialization of the child with intellectual incapacity. Adult examinees with psychological problems are not found. The respondents do not have serious emotional problems, they are optimistic, not inclined to state claims, active, successfully interact with people around, most of them possess a positive self-assessment. These characteristics are explained by the comprehensive program of social and psychological maintenance of families conducted at school. It is concluded that interconditionality of psychological well-being of children and their parents can and must be supported and adjusted by the school.Scientific novelty consists in the development of ideas to ensure positive socialization of families with children with disabilities.Practical significance. The found results can be used in special education, the implementation of social and psychological support of students with intellectual disabilities and their families.